New records of Collembola from marine littoral sand of Hainan Island, China, with description of a new Oudemansia species (Neanuridae: Pseudachorutinae) - Palacios-Vargas, José G.; Bu, Yun (Zootaxa, 2020)
One new species of springtail, Oudemansia chenorum sp. nov., is described and illustrated. Pseudanurida sawayai Schuster, 1965 is reported from Hainan Island for the first time. An identification key for the species of Oudemansia Schött, 1893 is provided and remarks are made on its peculiar morphology as well as that of close related genera. The presence of pseudocelli is further confirmed on members of the genus Oudemansia.